Field evaluation of newer insecticides for controlling pod fly (Melanagromyza obtusa) in pigeonpea (Cajanus cajan) - KATTI, GURURAJ; SACHIN, J N (The Indian Journal of Agricultural Sciences, 2013)
A Held trial was carried out during rainy season of 1991-92 and 1992-93 to evaluate the efficacy of 4 newinsecticides against pod fly (Melanagromyza obtusa Malloch) in 'Bahar' pigeonpea (Cajanus cajan Millsp.) in comparisonto insecticidal application. The insecticidal efficacy was assessed on the basis of pod and grain damage as wellas yield in different treatments. Results showed that carbosulfan @ 750 g a i/ha, benfuracarb @ 500 g a i/ha andetho fenprox @ 75 g a i/ha were highly effective in reducing pod (8.19-13.33%) and grain damage (4.33 - 12.33%) dueto pod fly compared with the recommended monocrotophos application (18.00 - 22.31 % pod damage; 16.33 - 18.95%grain damage). These treatments also showed yields (l 367 - 2373 kg/ha) on par with monocrotophos (1 767 - 2 708kg/ha) and were significantly superior to control (889 - 1 140 kg/ha).